Seasonal variation in the population of Black kite (Milvus migrans), inhabiting the Arid Zone of Rajasthan - Sharma, Sandeep; Soni, K. C (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
The population of Black kite (Milvus migrans) inhabiting rural and urban area of Churu city, Rajasthan was seasonally determined by the direct count method. The counting of the Black kite was made at roosting sites of Churu city (28o 15 N and 74o 55 E, 286 msl) and its out skirts area of 400 km2. Total 46 roosting sites were identified in the study area of which 34 were located in the urban area and 12 in the rural areas. It was found that number was relatively higher from June to September 2012, 2013 and 2014. However, the maximum numbers of Black kite were during August 2012 and July 2014 and minimum were during November 2012 and February 2012. The maximum number of adult was noticed in the rainy months of every year. A sharp decline in the juvenile population was observed from September 2014 to December 2014. Maximum 28 and 22 juvenile birds were observed in the month of August 2012 and July 2013 while the minimum 4 juvenile were observed in February 2012, March 2013 and November 2014. An average 25.41 ±SD12.4 and 42.33 ±SD 18.82in 2102, 27.33 ±SD 9.19 and 54.25 ±SD 14.9 in 2013, 20.90 ±SD 5.05and 43.08 ±SD 12.75in 2014 Black kites were observed in rural and urban areas, respectively. The maximum number of Black kites i.e. 134 individuals, occurred in the month of August 2012. But in general, the population remained more or less constant with seasonal variations involving dispersion during the monsoons and aggregation during the winters. The winter season adversely affects the population of Black kite in the study area because of the non-availability of preferential food.